Prevalence of post-menopausal symptoms in aged women who are staying at homes for old people: a descriptive study - Lydia Vieira Freitas; Thaís Marques Lima; Maria Leonor Costa de Moraes; Levânia Maria Benevides Dias; Priscila de Souza Aquino; Ana Karina Bezerra Pinheiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The study aimed at identifying the Blatt-Kupperman Menopausal Index (BKMI) and verifying the post-menopausal symptoms which are more prevalent in aged women who live in homes for old people. It's a quantitative descriptive, research, accomplished with institutionalized aged women from, Fortaleza/CE. The data were collected during the gynecologic consultation with the nurse, accomplished at the same institution in 2007. The results showed that the elderly were illiterate, unmarried, and had reached their menarche as they were 15 years of age. 17 women (63.0%), and 16 older women (59.3%) had reached menopause between 40 and 55 years of age. 24 women (88.9%) had presented light BKMI, with the absence of various symptoms, which may be the consequence of hormonal stability, result of a considerable time of menopause. The most prevalent symptoms were depression, nervousness, dizziness, arthralgia/myalgia and headache. We so conclude that the BKMI represents a valuable tool in the identification of post-menopausal symptoms and that its application in older institutionalized women allows the detection of factors often not approached in nursing consultation.